Combustion synthesis of porous ceramic Я- Si3N4 -based composites with the use of ferroalloys; Ceramics International; Vol. 47, iss. 24 - Bolgaru K. A. Konstantin Aleksandrovich; Reger A. A. Anton Andreevich; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Akulinkin A. A. Aleksandr Aleksandrovich (2021, 2021)
Title screen